2010
DOI: 10.1111/j.1468-1331.2010.03015.x
|View full text |Cite
|
Sign up to set email alerts
|

Patent foramen ovale is not associated with an increased risk of stroke recurrence

Abstract: Our data suggest that the risk of recurrent stroke in subjects with PFO is not significantly increased in comparison with subject without it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
12
0
2
Order By: Relevance
“…After retrieving the full-text version of the aforementioned 21 studies, 5 studies were excluded because the end points of medically treated patients were mixed with the end points of surgically treated (with percutaneous or open closure) patients, [26][27][28][29][30] 2 studies because of the absence of comparison group (patients without PFO or no shunt stratification) 31,32 and 1 study because the reported end point was the combined outcome of stroke, TIA, or death. 33 The remaining 13 studies 24,[34][35][36][37][38][39][40][41][42][43][44][45] and the available data from our study cohort were included both in the qualitative and quantitative synthesis, according to the presence of PFO (PFO present, PFO absent), the shunt size (small right-to-left shunt [RLS] versus moderate or large RLS, small or moderate RLS versus large RLS), and the available outcome data (stroke or TIA, stroke; Figure 1). The characteristics of the included studies are summarized in Table 1.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…After retrieving the full-text version of the aforementioned 21 studies, 5 studies were excluded because the end points of medically treated patients were mixed with the end points of surgically treated (with percutaneous or open closure) patients, [26][27][28][29][30] 2 studies because of the absence of comparison group (patients without PFO or no shunt stratification) 31,32 and 1 study because the reported end point was the combined outcome of stroke, TIA, or death. 33 The remaining 13 studies 24,[34][35][36][37][38][39][40][41][42][43][44][45] and the available data from our study cohort were included both in the qualitative and quantitative synthesis, according to the presence of PFO (PFO present, PFO absent), the shunt size (small right-to-left shunt [RLS] versus moderate or large RLS, small or moderate RLS versus large RLS), and the available outcome data (stroke or TIA, stroke; Figure 1). The characteristics of the included studies are summarized in Table 1.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…TCD or TEE protocol was sufficiently presented in 12 studies while the description was unavailable in 2 studies. 24,42 Loss to follow-up was reported in 8 studies 34,36,37,40,41,[43][44][45] and could not be evaluated in 2 studies. 24,25 Only 4 studies reported no losses to follow-up after initial recruitment.…”
Section: Risk Of Bias For Independent Studiesmentioning
confidence: 99%
See 3 more Smart Citations